The Effectiveness of Using Dialogue Journal Writing to Enhance Students’ Writing Skills at Lembaga Yasin alSys - Ferayanti, Leny (Lembaga Yasin AlSys, 2021)
This research investigated how the effectiveness of using the Dialogue Journal writing (dialogue journal writing) toward writing skills in recount text at Lembaga Kursus Yasin alSys students. This study concerned on find out the effectiveness of dialogue journal writing and explaine the five aspects of writing skill as proposed by Anderson, i.e. grammar, vocabulary, mechanics, fluency and form. This research is classified as experimental study which was done with the participation of 26 students class as the object of the study. The data obtained during the research were in quantitative and qualitative forms. The qualitative data were acquired from the field notes, interview transcripts, and photographs. The quantitative ones were collected from the results of the students’ pre-test and post-test and also from the students’ texts written in their dialogue journal writing books which were analyzed to get the mean scores to be compared and then determine the gain scores . In regard to the actions performed in two cycles, the use of dialogue journal writing was effective in improving the students’ skills in recount texts based on the following evidences. First evidence, the researcher found that from the data description demonstrated 0.004 score in Asymp Sig (2-tailed), because the Asymp Sig (2-tailed) score is lower than 95% the confidence interval that is 0.05, then the data is significant. Second evidence, from six male and female responses consisted lowest to highest sampling toward dialogue journal writing was found that there were five aspects appeared, i.e grammar, vocabulary, mechanic, fluency, and form. Following the result of this research, it could contribute to language teaching especially in writing sill.